Physical Exercise Reduces the Expression of RANTES and Its CCR5 Receptor in the Adipose Tissue of Obese Humans - Engin Baturcam; Jehad Abubaker; Ali Tiss; Mohamed Abu-Farha; Abdelkrim Khadir; Fahad Al-Ghimlas; Irina Al-Khairi; Preethi Cherian; Naser Elkum; Maha Hammad; Jeena John; Sina Kavalakatt; et al. (Mediators of Inflammation)
RANTES and its CCR5 receptor trigger inflammation and its progression to insulin resistance in obese. In the present study, we investigated for the first time the effect of physical exercise on the expression of RANTES and CCR5 in obese humans. Fifty-seven adult nondiabetic subjects (17 lean and 40 obese) were enrolled in a 3-month supervised physical exercise. RANTES and CCR5 expressions were measured in PBMCs and subcutaneous adipose tissue before and after exercise. Circulating plasma levels of RANTES were also investigated. There was a significant increase in RANTES and CCR5 expression in the subcutaneous adipose tissue of obese compared to lean. In PBMCs, however, while the levels of RANTES mRNA and protein were comparable between both groups, CCR5 mRNA was downregulated in obese subjects (P<0.05). Physical exercise significantly reduced the expression of both RANTES and CCR5 (P<0.05) in the adipose tissue of obese individuals with a concomitant decrease in the levels of the inflammatory markers TNF-α, IL-6, and P-JNK. Circulating RANTES correlated negatively with anti-inflammatory IL-1ra (P=0.001) and positively with proinflammatory IP-10 and TBARS levels (P<0.05). Therefore, physical exercise may provide an effective approach for combating the deleterious effects associated with obesity through RANTES signaling in the adipose tissue.